Financial distress, audit committee, profit and loss, audit delay: An empirical study - Putri Nurmala; Rizki Wahyudi (President University Press, 2022)
The purpose of this study is to determine whether or not audit delay is caused by financial stress, the audit committee, or the profit and loss of the company. This study also considered a number of independent criteria, such as the severity of the financial situation, participation in the audit committee, and profit and loss. In addition to this, it incorporates the dependent variable known as audit delay. In this work, quantitative descriptive research is used. Secondary data are collected for the purpose of this investigation, and the documentation process serves as the approach for gathering data. This research focused on forty different property and real estate firms that were traded on the Indonesia Stock Exchange between the years 2016 and 2020. According to the conclusions of the research, businesses that experience a rise in profits will have a shorter audit delay, whereas businesses that experience a rise in losses will have a longer audit delay. In the meantime, financial trouble and having an audit committee don't have much to do with audit delay.